Factors Associated with Attractiveness and Retention in Nursing - Salminen-Tuomaala, Mari (European Journal of Applied Sciences, 2023)
The study describes factors associated with the attractiveness and retention of nursing, as experienced by registered nurses (n=24) upgrading their education to a Master’s Degree at a University of Applied Sciences in Finland. The study aims at producing knowledge that can be used to improve nurse retention and the attractiveness of the clinical nursing profession. The 6-3-5 Brainwriting Method of Rohrbach was used to collect data which was analysed using inductive content analysis. The findings support previous international literature. Promotion of appreciation, professional development and wellbeing at work through optimal working conditions, increased influence and compassionate, supportive leadership were among the most significant, recurrent themes in the participant contributions. Further work is required to increase the appreciation of nursing in order to retain nurses and attract new applicants. The measures suggested in this research include the development of more compassionate leadership, professional development options and optimal conditions to ensure wellbeing at work.